MENGINTEGRASIKAN NILAI EKONOMI ISLAM DALAM REKONSTRUKSI SISTEM EKONOMI DI INDONESIA (Solusi Alternatif Mencari Jalan keluar dari Krisis Ekonomi) - Munim, Fathan (Khatulistiwa, 2012)
The reform movement that has swept Indonesia since 1998 has not yet had a significant impact on the improvement of the government’s performance especially with regard to the economic field. The ongoing economic crisis and the rising inflation accompanied by a high rate of unemployment and crime are the multiplier effects of the government’s failure in implementing economic policies. The effects also indicate that capitalism has failed to provide prosperity for all. Capitalism has, in fact, created a gap between the developed and the developing countries. This writing tries to analyze and formulate the concept of integrating Islamic economic values in order to find a solution for the reestablishment of an economic concept which is capable of overcoming the ongoing economic crisis in this country, hopefully.